Comparing the effectiveness of an internet-delivered Acceptance and Commitment Therapy (ACT) intervention with a wait list control on health related quality of life among adults with multimorbidity: Study protocol for a randomised controlled trial - Brian Slattery (Frontiers Media S.A., 2015)
Multimorbidity is defined as the coexistence of two or more conditions within one person, where no one condition is primary. Chronic Pain (CP) is found to be one of the most frequent conditions represented amongst multimorbidities. CP and in particular MM, can have significant debilitating effects on a persons' Health Related Quality of Life (HRQoL). There is a dearth of research however, targeting and improving HRQoL for people living with MM, were CP is a feature. Aim of Investigation: This study will compare the clinical- effectiveness of an online ACT intervention with a waitlist control condition in terms of increasing health related quality of life among people with multimorbidities, were chronic pain is a feature. Methods: Adult participants with non-malignant pain that persists for at least three months and at least one other condition as diagnosed by a doctor will be randomised to one of two study conditions. The experimental group will undergo an 8-session internet-delivered ACT-programme over an 8-week period. A wait-list group will be offered the ACT intervention after the 3-month follow-up period. Results: Participants will be assessed pre-intervention, post-intervention and at a 3-month follow-up. HRQoL will be the primary outcome. Secondary outcomes will include: pain intensity; depression; acceptance of chronic pain and symptoms of other morbidities. Conclusions: At present, we are in the early stages of participant recruitment. As a result, the focus of this poster will be on describing the methodological and recruitment processes for the current study.